Secure data outsourcing scheme in cloud computing with attribute-based encryption. (2018) - Zhu, Shuaishuai; Han, Yiliang
Cloud computing is clearly becoming one of the dominating infrastructures for enterprises as long as they are end users. But in the view of cloud users, such as traditional big companies, data in cloud computing systems tend to be out of control and its privacy fragile. A mechanism to guarantee the ownership of data is required. In this paper, we analyse a couple of recently presented scalable data management models to describe the storage patterns of data in cloud computing systems. Then we define a new tree-based data set management model to solve the storage and sharing problems in cloud computing. A couple of operation strategies including data encryption, data boundary maintenance, and data proof are extracted from the view of different entities in the cloud. Based on these strategies, a flexible data management mechanism is designed in the model to guarantee entity privacy, data availability and secure data sharing.